Al-doped nickel sulfide nanosheet arrays as highly efficient bifunctional electrocatalysts for overall water splitting. Issue 47 (8th December 2020) - He, Wenjun; Wang, Fangqing; Jia, Dongbo; Li, Ying; Liang, Limin; Zhang, Jun; Hao, Qiuyan; Liu, Caichi; Liu, Hui; Zhao, Jianling
Abstract : The development of low-cost, high-activity, durable non-precious metal bifunctional electrocatalysts is of great importance in the production of hydrogen by water electrolysis. Abstract : The development of low-cost, high-activity, durable non-precious metal bifunctional electrocatalysts is of great importance in the production of hydrogen by water electrolysis. In this work, we have prepared new Al-doped Ni3 S2 nanosheet arrays grown on Ni foam (Al-Ni3 S2 /NF) as an excellent bifunctional electrocatalyst in the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The Al-Ni3 S2 /NF electrode obtained only requires extremely low overpotentials of 86 and 223 mV for the HER and OER to achieve a current density of 10 mA cm −2 in 1 M KOH, respectively. Moreover, the electrolytic cell assembled using this electrode as both cathode and anode provides a current density of 10 mA cm −2 at an extremely low battery voltage of 1.58 V relative to that with Ni3 S2 /NF (1.71 V). Additionally, both experimental results and theoretical calculations reveal that the increased electrochemical active surface area and optimized intermediate adsorption free energies are responsible for the enhanced electrocatalytic performance. This work provides a promising bifunctional electrocatalyst for water electrolysis in alkaline media with broad application prospects.